Stability of pollination services decreases with isolation from natural areas despite honey bee visits - Garibaldi, Lucas A.; Steffan-Dewenter, Ingolf; Kremen, Claire; Morales, Juan M.; Bommarco, Riccardo; Cunningham, Saul A.; Carvalheiro, Luísa G.; Chacoff, Natacha P.; Dudenhöffer, Jan H.; Greenleaf, Sarah S.; Holzschuh, Andrea; Isaacs, Rufus; et al. (Ecology letters, 2011)
Ecology Letters (2011) 14: 1062–1072 Sustainable agricultural landscapes by definition provide high magnitude and stability of ecosystem services, biodiversity and crop productivity. However, few studies have considered landscape effects on the stability of ecosystem services. We tested whether isolation from florally diverse natural and semi‐natural areas reduces the spatial and temporal stability of flower‐visitor richness and pollination services in crop fields. We synthesised data from 29 studies with contrasting biomes, crop species and pollinator communities. Stability of flower‐visitor richness, visitation rate (all insects except honey bees) and fruit set all decreased with distance from natural areas. At 1 km from adjacent natural areas, spatial stability decreased by 25, 16 and 9% for richness, visitation and fruit set, respectively, while temporal stability decreased by 39% for richness and 13% for visitation. Mean richness, visitation and fruit set also decreased with isolation, by 34, 27 and 16% at 1 km respectively. In contrast, honey bee visitation did not change with isolation and represented > 25% of crop visits in 21 studies. Therefore, wild pollinators are relevant for crop productivity and stability even when honey bees are abundant. Policies to preserve and restore natural areas in agricultural landscapes should enhance levels and reliability of pollination services.